Construction of Optical Topological Cavities Using Photonic Crystals - Yuan, Meng; Xu, Tao; Hang, Zhi Hong (Frontiers in Physics, 2021)
A novel design of Fabry-Pérot optical cavity is proposed utilizing both the topological interface state structures and photonic bandgap materials with controllable reflection phase. A one-to-one correspondence between the traditional Fabry-Pérot cavity and optical topological cavity is found while the tunable reflection phase of the photonic crystal mirrors provides an extra degree of freedom on cavity mode selection. The relationship between Zak phase and photonic bandgap provides a theoretical guidance to the manipulation of reflection phase on photonic crystals. The dispersions of interface states with different topology origins are explored. Linear interfacial dispersion emerging in photonic crystals with valley spin Hall effect leads to an extra n=0 cavity mode comparing to the Zak phase induced deterministic interface states with quadratic dispersion. The frequency of n=0 cavity mode is not affected by the cavity length whose quality factor can also be tuned by the thickness of the photonic crystal mirrors. With the new help of topology photonics on tuning reflection phase and dispersion relationship, we hope our results can provide more intriguing ideas to construct topological optical devices.